CONSTRAINTS/CHALLENGES FACED BY FARMERS IN ADOPTION OF MICRO IRRIGATION IN RANGA REDDY DISTRICT OF TELANGANA - P. RADHIKA; K. SUPRIYA, VISHWARADHYA, D. SRINIVASA REDDY (The Journal of Research, PJTSAU, 2021)
Micro irrigation is a modern method of irrigation; by this method water is irrigated through drippers, sprinklers, foggers and by other emitters on surface and subsurface of land. Water is a relatively scarce resource in India since we have 17 per cent of the world’s population and only four per cent of the usable fresh water at global level. Irrigation is the sector that uses water the most. Nearly 80 per cent of the world’s water resources are used for irrigation.